Nilai Budaya Kearifan Lokal Tri Hita Karana Dalam Penentuan Harga Jual (Studi Etnometodologi Pada Pedagang Buah-Buahan Pasar Banyuasri - Putu Eka Wati; Ni Wayan Yulianita Dewi; Putu Ria Astria (UNHI Press, 2024)
Abstract: The study of accounting practices in local wisdom is always interesting to research. Understanding that every activity requires accounting, based on a version that is appropriate to the culture and beliefs of the local community. Pricing is used as a bridge by sellers to achieve maximum material profits by keeping costs as low as possible. As a result, price wars are a familiar sight today. There is no longer any togetherness and brotherhood among the sellers from the sales activities carried out. The aim of this research is to reveal the cultural values of local wisdom contained in determining the selling price of fruit, which is implemented by Banyuasri Market traders based on the local wisdom values of Tri Hita Karana. Data analysis uses the hermeneutic analysis method of intentionalism. Based on the findings in this research, the reality of selling prices implemented by fruit traders at Banyuasri Market depicts a complete form of selling price and is based on the values of the Tri Hita Karana philosophy. The elements of material values (not wealth), the value of submission to the Creator, the value of environmental preservation, and the value of togetherness between fellow humans or traders are a unified whole that cannot be separated.